2018
DOI: 10.1016/j.ympev.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for mtDNA capture in the jacamar Galbula leucogastra/chalcothorax species-complex and insights on the evolution of white-sand ecosystems in the Amazon basin

Abstract: Jacamar species occur throughout Amazonia, with most species occupying forested habitats. One species-complex, Galbula leucogastra/chalcothorax, is associated to white sand ecosystems (WSE). Previous studies of WSE bird species recovered shallow genetic structure in mtDNA coupled with signs of gene flow among WSE patches. Here, we characterize diversification of the G. leucogastra/chalcothorax species-complex with dense sampling across its distribution using mitochondrial and genomic (Ultraconserved Elements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 92 publications
2
18
0
Order By: Relevance
“…Even so, one characteristic in all these cases is the absence of reciprocal monophyly in the mitochondrial genealogy of the lineages, which would be consistent with ILS (McKay & Zink, ), although this is not true of the pattern found in the B and C lineages (Figure ). However, more recent studies have indicated that the disagreement between mitochondrial and nuclear phylogenies may be a consequence of past introgression events that resulted in the sequestering of the mtDNA of the established populations (Ferreira et al, ; Sullivan et al, ). In this case, with sufficient divergence time, unrelated lineages in a multilocus species tree may become more closely related from a mitochondrial perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, one characteristic in all these cases is the absence of reciprocal monophyly in the mitochondrial genealogy of the lineages, which would be consistent with ILS (McKay & Zink, ), although this is not true of the pattern found in the B and C lineages (Figure ). However, more recent studies have indicated that the disagreement between mitochondrial and nuclear phylogenies may be a consequence of past introgression events that resulted in the sequestering of the mtDNA of the established populations (Ferreira et al, ; Sullivan et al, ). In this case, with sufficient divergence time, unrelated lineages in a multilocus species tree may become more closely related from a mitochondrial perspective.…”
Section: Discussionmentioning
confidence: 99%
“…If nuclear sequence data disagree with the mitochondrial data we present, the first hypothesis could easily account for this pattern through gene flow and mitochondrial capture from one species to the other (e.g. Hird & Sullivan 2009, Irwin et al 2009, Ferreira et al 2018. Expanded geographic sampling, particularly from western populations of E. papuana in the Bird's Head region of New Guinea will be necessary to fully explore this hypothesis.…”
Section: Discussionmentioning
confidence: 75%
“…Another possible explanation to the nuclear-mitochondrial discordance may be a mitochondrial capture event early in the evolution of the family (cf. Ferreira et al 2018 ), but the fact that the rooting depends on which codon positions are analyzed makes saturation more likely.…”
Section: Discussionmentioning
confidence: 99%